Drug Involvement among Undergraduate Students: Age and Gender Differences (Journal of Guidance and Counselling Studies, 2025)
This study investigated drug use among undergraduate students, looking at age and gender disparities and if these factors affect drug use differently among undergraduate students.  Two research questions and hypotheses guided the study. The study employed a descriptive survey research design. A sample of 360 students were selected using multi-stage random sampling technique from a population of 47,233 undergraduate students of Nnamdi Azikiwe University, Awka and Chukwuemeka Odumegwu Ojukwu University, Igbariam campus Anambra State to ensure the representation of age and gender differences. The instrument for data collection was the adolescent drug involvement scale. Data collected were analyzed using descriptive and inferential statistics. Mean scores were utilized to answer the research questions while t-test was used to test the hypothesis at significant level of 0.05. The result of the findings revealed that there are no significant age differences in undergraduate students’ drug involvement and that male undergraduate students are more involved in drug than female. It was recommended that there should be implementation of Age-Specific and Gender-Sensitive Prevention Programmes that will develop prevention programs that cater to the unique needs and vulnerabilities of different ages; Provision of Access to Counseling and Mental Health Services ensuring that undergraduate students have access to confidential counseling and mental health services, including substance abuse treatment and support groups etc.